Dinâmica espaço-temporal, quantificação de danos e perdas e influência do cancro (Chrysoporthe cubensis) no acúmulo de biomassa e fixação de carbono em seis genótipos de eucalyptus spp - Tumura, Karina Goulart [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Eucalyptus' culture is one of the most important in Brazil being a source of renewable energy and wood. In addition, it supports important agro-industrial processes for the production of pulp, paper and essences. Eucalyptus, like any other plant species, can be infected by many pathogens, especially fungi, from nurseries to adult plantations. In this work, the causal agent of basal canker, Chrysoporthe cubensis, were studied. This disease has a wide geographical distribution, occurring from the southern end of São Paulo State to the Amazon, observing sensitive damages in low-lying regions of Espírito Santo State, Rio Doce Valley in Minas Gerais State and Reconcavo Baiano. Its symptons are quite varied and the fungi can attack plants from five months of age until the end of forest rotation. Young plants with small diameters may be girdled at their base by canker, being put to death. Attack in older plants may result in low or heavy typical cankers, that can be found at different heights of the trunk. The work was conducted in the area of EUCFLUX project, which were established with 16 clones in 10 experimental plots with different soil conditions and elevation. Studies of disease influence in carbon fixation and biomass accumulation are scarce, therefore, the objectives of this work were: a) verify the susceptibility to basal canker of the six clones with higher productivity used in experimental plots of EUCFLUX; b) conduct the spatiotemporal study of the disease and; c) verify the influence of basal canker in the accumulation of biomass and carbon fixation of the attacked plants. Incidence of the disease were evaluated in three plots and these data were the basis for spatiotemporal analysis. To determine biomass parameters, inventory was done in the same three plots and volume and biomass equations were adjusted. In addition, specific gravity of the wood and bark were calculated to healthy ...

A cultura do eucalipto é uma das mais importantes do Brasil, constituindo-se em fonte de energia e madeira renovável, suportando importantes processos agroindustriais, dentre eles, a produção de celulose, papel e essências. O eucalipto, como outras espécies vegetais, é infectado por diversos patógenos, principalmente fungos, desde o viveiro até plantios adultos. Neste trabalho, será estudado o agente causador do cancro basal, Chrysoporthe cubensis. Esta doença possui ampla distribuição geográfica, ocorrendo desde o extremo sul do Estado de São Paulo até a Amazônia, observando-se prejuízos em regiões de baixa altitude de Espírito Santo, do Vale do rio Doce em Minas Gerais e Recôncavo Baiano. Sua sintomatologia é bastante variada, podendo atacar plantas de cinco meses de idade até o final da rotação. As plantas jovens, por apresentarem diâmetros reduzidos, podem ser aneladas na sua base pelo cancro, sendo levadas à morte. Do ataque em plantas mais velhas resultam lesões com pouco ou abundante trincamento até cancros típicos, podendo ser encontrados a diversas alturas do tronco. O local escolhido para a realização do trabalho, foi a área do projeto EUCFLUX, onde estão implantadas parcelas experimentais com 16 materiais genéticos, em diferentes condições de solo e altitude. Os estudos sobre a influência de doenças no acúmulo de biomassa e fixação de carbono são escassos, sendo assim, os objetivos desse trabalho foram: a) verificar a suscetibilidade ao cancro basal dos seis clones com maior produtividade utilizados nas parcelas experimentais do EUCFLUX; b) proceder o estudo espaço-temporal da doença e c) verificar a influência do cancro basal no acúmulo de biomassa e fixação de carbono das plantas atacadas. Foram avaliadas três repetições quanto à incidência da doença, sendo que tais dados formaram a base para a análise espaço-temporal...
Space-time dynamics, damage and losses quantification and canker influence (chrysoporthe cubensis) in biomass acumulation, carbon fixation in six eucalyptus' genotypes
Keywords: Eucalipto - Doenças e pragas; Cancro (Fitopatologia); Biomassa; Biomass